Old religion, new spirituality : implications of secularisation and individualisation in Estonia - Altnurme, Riho (2021)
"This book answers two important questions about Estonia. The first question - why is Estonia so secularised in terms of de- institutionalisation and dechristianisation? - is the thread running through all of the chapters, from the historical discussion to the contemporary situation. The second question pertains to the consequences of secularisation: what is the link between Estonia's secularity and today's picture of individualised religiosity in the country? The results of this research project provide fresh results from surveys, archival work and analysis by experienced researchers and doctoral students"